Mental Health, Social Mirror
XXII, 472 p.
Keywords: While mental health figured prominently in the writings of classical sociologists, contemporary sociologists often view research on mental health as peripheral to the "real work" of the discipline. The essays in this volume reassert the centrality of research in mental health to sociology. First, they articulate the contributions that mental health research has made and can make to resolving key theoretical and empirical debates in important areas of sociological study. Second, they draw from mainstream theories and concepts to reconsider the potential of sociology to provide answers to critical questions regarding the social origins of and social responses to mental illness. As reflected in the title, the sociological study of mental health provides a reflection of the central processes that characterize our society.